2017
DOI: 10.1177/1059840517725789
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Compassion Fatigue and Stress of Special Education Teachers and Professional Staff Using Mindfulness and Prayer

Abstract: Alternative therapies are promising nursing interventions for improvement of compassion fatigue in educators working in special education. A convenience sample of 27 teachers and professional staff working in special education participated in a quasi-experimental pilot study and completed a pre/posttest of demographic questions, the Perceived Stress Scale (PSS) (10-item) and Professional Quality of Life (ProQOL). All attended a presentation on stress, compassion satisfaction (CS), mindfulness, prayer, and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 29 publications
2
31
1
2
Order By: Relevance
“…Our study confirms also that the results of a quasiexperimental (pre/posttest) pilot study showing a significant improvement of mental health outcomes occurred in a convenience sample of 27 teachers and professional staff working in special education with the use of mindfulness and prayer (Sharp Donahoo et al, 2018). Both meditation and prayer are mind-body-spirit interventions and just differ in the conditioning of the mind.…”
Section: Discussionsupporting
confidence: 86%
“…Our study confirms also that the results of a quasiexperimental (pre/posttest) pilot study showing a significant improvement of mental health outcomes occurred in a convenience sample of 27 teachers and professional staff working in special education with the use of mindfulness and prayer (Sharp Donahoo et al, 2018). Both meditation and prayer are mind-body-spirit interventions and just differ in the conditioning of the mind.…”
Section: Discussionsupporting
confidence: 86%
“…These results are also in favor of Bazzano's perspective that a community‐based mindfulness training program can be an effective intervention in decreasing stress and improving psychological well‐being for caregivers of children with developmental disabilities (Bazzano et al, ). However, results do not support the study by Sharp Donahoo et al () that the intervention of mindfulness and alternative therapies were ineffective in alleviating burnout. Possible explanations are the limitations in Sharp Donahoo et al () study design: Timings of the tests were inappropriate and interventions that the participants received were inconsistent, constricting the reliability and validity of research results.…”
Section: Discussioncontrasting
confidence: 84%
“…In addition, community‐based mindfulness intervention has been established as an effective program for reducing the stress and improving the psychological well‐being of parents or caregivers of children with developmental disabilities (Bazzano et al, ). However, a study has found that after 4–5 weeks of mindfulness intervention, burnout increased in special education teachers (Sharp Donahoo, Siegrist, & Garrett‐Wright, ). The results of this study need to be treated with caution due to its procedural limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of the trauma-affected classroom, the opposite of compassion fatigue is compassion satisfaction, defined as the pleasure one derives from being able to do one's work well, being satisfied by the helping aspects of the work, and feeling invigorated by the work itself (Sharp Donahoo et al, 2017;Stamm, 2005). People who work in traumaaffected environments report compassion satisfaction when they are encouraged to incorporate new ways of working into their practice, are supported to deal with professional adversity, feel happy and successful when continuing their work, and believe their work makes a difference (Stamm, 2005(Stamm, , 2010.…”
Section: Psychodynamic Existential Perspectives To Understand Meaningmentioning
confidence: 99%